White Matter Degeneration Pathways Associated with Tau Deposition in Alzheimer's Disease. (20th December 2022) - Tian, Jianqiao; Reid, Robert I.; Przybelski, Scott A.; Raghavan, Sheelakumari; Gebre, Robel K; Graff‐Radford, Jonathan; Lowe, Val J.; Kantarci, Kejal; Knopman, David S.; Petersen, Ronald C.; Jack, Clifford R.; Vemuri, Prashanthi
Abstract: Background: The dynamics of white matter (WM) changes are understudied in Alzheimer's disease (AD). Leveraging tau deposition measured from Tau‐PET, our goal was to study the association between tau and white matter health using NODDI from multi‐shell diffusion MRI (dMRI). Specifically, we focused on the Neurite Density Index (NDI) from NODDI, which in WM captures the signal from axons. Method: We identified 251 participants (126 cognitively normal, 58 MCI, 67 dementia) from the Mayo ADRC and Mayo Clinic Study of Aging with Aβ‐PET, Tau‐PET, and multi‐shell dMRI who were Aβ‐positive (mean age of 77 years and 55% male). We limited to Aβ‐positive participants because Aβ deposition accelerates tau deposition. For Tau‐PET, we estimated SUVRs from three regions corresponding to Braak I/II, III/IV, and V/VI (Figure 1. a ). To understand the associations between Tau‐PET SUVRs at three Braak regions and NDIs at 30 candidate WM tracts, we implemented three analyses methods ‐ Pearson correlation, linear regression, and multilayer perceptron machine learning regression. Result: Higher tau burden in all three Braak regions was associated with lower neurite density in 10 significant WM tracts (Table 1 ). Interestingly, uncinate fasciculus (UNC) was found significantly associated with all three Braak regions. All three analysis methods consistently showed differential involvement of WM pathways for Braak staging such as ‐ Cingulum adjoining Hippocampus (CGH) for Braak I/II regions, Medial Temporal WM (MTWM) for Braak III/IV regions, and Inferior Occipital WM (IOWM) for Braak V/VI regions (Figure 1. b ). The linear regression and machine learning regression models also suggested that WM measurements reflected 18‐35% of variance due to tau deposition Conclusion: We found that CGH and UNC WM were the most impacted ROIs associated with Braak I/II regions as expected. UNC, directly connecting anterior temporal lobes to the orbitofrontal cortex, was a key WM tract identified as important for all Braak I‐VI regions and warrants further investigation in the study of AD progression. This study highlights the significant impact tau deposition may have on WM. This work also demonstrates the feasibility of using NODDI as an informative supplementary imaging modality for monitoring AD progression.